THE ROLE OF KADIRUN YAHYA IN EDUCATION - Hasan Asari; Danny Abrianto; Ali Imran Sinaga (Proceeding International Seminar of Islamic Studies, 2021)
Kadirun Yahya is a figure in the world of education and started to establish and manage non-formal educational institutions, namely an educational institution and process that combines or integrates science and religion, between academic and spiritual, and between worldly and ukhrawi life. The non-formal educational institutions that were established became the forerunners to establish several formal educational institutions consisting of Kindergarten, Elementary School (SD), Junior High School (SMP), to Senior High School (SMU), Vocational High School (SMK). This formal educational institution under the auspices of Panca Budi College is managed professionally and with pure management. Likewise with the learning tools, gradually leading to modern learning devices that are adapted to multimedia and digital developments. Based on the research results, it can be seen from the criteria regarding the existence of non-formal education, slightly different from the formal education institutions established by Kadirun Yahya. In fact, the non-formal educational institutions that he founded tend to prepare for the afterlife, not to prepare a ready-made workforce. But what is unique is that he still facilitates his students to get formal education at school and even become a bachelor. The non-formal educational institutions that have been established by Kadirun Yahya are as follows: First, Houses of Worship in the form of Surau-Surau. The purpose of this surau-surau was established as a place to do and practice dhikrullah and mental spiritual training center training (i'tikaf / suluk). Second, the Youth Generation. The youth development activities carried out by Kadirun Yahya are placed in various existing surau. This activity is an effort to help underprivileged youth. They are given guidance in the form of talent development activities, while still carrying out worship, as well as guarding the mosque where they are stationed.Keywords: Educational Institutions, Modern Sufism, Education